KEANGKUHAN BERUJUNG KEMATIAN : HERMENEUTIK KRITIK HISTORIS TENTANG KISAH HAMAN DALAM ESTER 7:1-10 - Merline Mesti Kukus; Argenliano Ferdinandus Tawaris (DA'AT : Jurnal Teologi Kristen, 2025)
The Jews in Persia suffered endlessly as a result of Haman's regulations. The compound word "suffering" here refers to the Jews' bodily and spiritual characteristics. Captured members of a second-class society, they lack the strength to fight for their own fate. Their lives are totally dependent on what God accomplishes. In addition to preventing the destruction of the Jewish country, Esther's liberation battle defended the rights of the weak and defenseless, the oppressed, and the second-class society. Finally, Haman, who had planned to destroy the Jews, was present at the second banquet of King Ahasuerus and Queen Esther. At first, Esther said nothing, but finally revealed that she was Jewish and asked the king to save her and her people from the threat of Haman. King Ahasuerus became angry and decided to punish Haman in the way he had planned for Mordecai, one of his uncles. This event marks a turning point in the story, where the threat to the Jews begins to be overcome and Haman accepts the consequences of his actions. To understand the text, the author uses the hermeneutic method of historical criticism and then studies it theologically in the Book of Esther 7:1-10, which ultimately leads to the power of God.